-5x+2(x+3)=-3

Simple and best practice solution for -5x+2(x+3)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+2(x+3)=-3 equation:



-5x+2(x+3)=-3
We move all terms to the left:
-5x+2(x+3)-(-3)=0
We add all the numbers together, and all the variables
-5x+2(x+3)+3=0
We multiply parentheses
-5x+2x+6+3=0
We add all the numbers together, and all the variables
-3x+9=0
We move all terms containing x to the left, all other terms to the right
-3x=-9
x=-9/-3
x=+3

You can always share this solution

See similar equations:

| -3z^2=9z-7 | | 16/(x+7)=2/6 | | 5/2x+4/3x=2 | | -5w^2+2w-10=0 | | -20x^2-50x+200=30x-10 | | -2/3x+9=7/8+1/2x | | 4+(2*8)=x | | (6+14)*2=x | | 5+x=19-4+5 | | v+5=15 | | (6x-10)=5x-14 | | 3(x+6)-7=-18 | | 13=y+10 | | 4+x=14-1+8 | | 3x^2+5x^2-4x-4=0 | | 11/6? =n+97? | | x^2+20x+100=1 | | x/5+4=27/5 | | -9y+46=-5(y-2) | | 7x+4x-3+2=16 | | (9y+10)-(3y-3=) | | 22=(-5)+3x-6 | | 2c/3?4c/5=7 | | -5x+3(x+8=36 | | 6(x+1)=10x-42 | | -5(-3+2n)=7(3-n) | | 15p^2-27p-6=0 | | 3x-(-x-9)=2(x+5) | | 5x+7=117 | | (5/6)x-5=5 | | (2/3)x+(3/4)=51 | | 7(x+7)=6x+9 | | 3v-24=-6(v-5) | | 5(-1y+4)=35 | | 3x²+10=4x | | 5(x+2=50 | | 5(x—2)=50 | | -1(-3y+-2)=-7 | | 1(x+1)=7 | | 1(x+1))=7 | | 1(x-(-1))=7 | | 8n-14n-3n^2+2=0 | | 8=w.2+2 | | -3(x-(-1))=-3 | | 10-8x=-15+11x | | 12y-8+4y+y-2=0 | | 5x+3(.5x)=3,000 | | -3(-3y+5)=-60 | | 25=-0,003x2+0,0638x+40 | | 12y-8y+4y+y-2=0 | | -2(z+4)=-37 | | 15x+5(.5x)=6067 | | 6x+36=-3(x+9) | | -6(u-2)=-8u+14 | | 2w+9=9(w+8) | | 30-5z=8(9z+7) | | C/4+76=4b | | 4x+9x-8x=6+4 | | 8x-90=-2 | | 6+1/2x=x(2) | | 3/2a+1/4=5/8 | | v^2+15v+59=0 | | 5y×2y=-24 | | 3-x/5=10 | | -4(w-9)=3w+8 |

Equations solver categories